2013
DOI: 10.1371/journal.pone.0060941
|View full text |Cite
|
Sign up to set email alerts
|

Latent Microsporidiosis Caused by Encephalitozoon cuniculi in Immunocompetent Hosts: A Murine Model Demonstrating the Ineffectiveness of the Immune System and Treatment with Albendazole

Abstract: BackgroundMicrosporidia are obligate intracellular parasites causing severe infections with lethal outcome in immunocompromised hosts. However, these pathogens are more frequently reported as latent infections in immunocompetent individuals and raises questions about the potential risk of reactivation following induced immunosuppression.AimsTo evaluate the possibility latent microsporidiosis, efficacy or albendazole, and reactivation, the authors monitored the course of E. cuniculi infection in immunocompetent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 39 publications
(46 reference statements)
14
50
1
Order By: Relevance
“…A similar effect was reported in cases of HIV-infected patients, who cleared the microsporidiosis after immune reconstitution in the absence of specific antiparasitic treatment (16). The same results were obtained experimentally using murine model hosts (9). Taking into account that only partially effective chemotherapy against Encephalitozoon spp.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…A similar effect was reported in cases of HIV-infected patients, who cleared the microsporidiosis after immune reconstitution in the absence of specific antiparasitic treatment (16). The same results were obtained experimentally using murine model hosts (9). Taking into account that only partially effective chemotherapy against Encephalitozoon spp.…”
supporting
confidence: 71%
“…However, since organ donors are not routinely tested for microsporidial infection, the organ transplant recipient could become infected via a microsporidium-positive graft. Furthermore, due to decreased recipient immunity, microsporidia could reactivate (9). The infection could also be responsible for decreased function of graft or cause pathologies without an identified causative agent, such as in the patient in our study.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…For example, fumagillin is one of the few compounds that are effective in killing some species of microsporidia but unfortunately it is toxic to humans [5]. Some groups report that the prevalence of microsporidia infections in humans increasing, with many individuals carrying latent and asymptomatic infections [6-8]. For further details on the clinical relevance of microsporidia, we refer readers to a recent review of this topic [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, it has been reported that microsporidial infections can cause complications in non-HIV populations, especially those receiving organ transplants (6)(7)(8)(9). In a very recent study, Kotkova et al demonstrated that microsporidiosis was probably a latent infection, which could reactivate in an immunocompromised situation, further highlighting the importance of studying the immune response against this ubiquitous pathogen (10). An experimental murine model using E. cuniculi mimics the human infection and has commonly been used to investigate the host immune response (11).…”
mentioning
confidence: 99%